The Cascade C─H functionalization with sequential hydroxylation and oxidation through heterogeneous BINAP‐copper on hydrotalcite. Issue 7 (19th March 2020) - Zhang, Qiaohong; Wang, Huibin; Hu, Wenkang; Xu, Xiaqing; Xu, Zhaojun; Chen, Chen; Wang, Dawei
Abstract: BACKGROUND: Aromatic thioether derivatives exist widely in natural products and have significant applications in modern synthesis and the pharmaceutical industry; for example, 2‐sulfanylphenols and arylthioquinones are important intermediates in the processing of anticancer, antibiotic, antivirus and antimalarial drugs. Direct C─H hydroxylation was considered as one of the efficient methods for the synthesis of these compounds. Homogeneous transition metal catalysts usually were used through a cross‐coupling of halogen‐substituted phenols with thiophenols. However, from the perspectives of sustainable development and easy recovery, it is necessary to develop an efficient and recoverable catalytic system to realize the synthesis of aromatic thioether derivatives with good efficiency and recyclability. RESULTS: The heterogeneous catalyst [Cu(binap)I]2 @HT in the present work showed good catalytic activity for the C─H hydroxylation of benzenethiol and phenylboronic acid. The catalytic system was tolerant to various substituents including alkyl, alkoxy, ester, halogen or trifluoromethyl on the phenyl ring of the thiophenols or arylboric acids. In addition to electron‐donating groups, the products with strong electron‐withdrawing groups, such as methyl formylate and trifluoromethyl also were achieved with good yields at 90 °C for 12 h (68% and 66%, respectively). Repeated experiment results showed that the catalyst could be reused at least five times without obvious decrease in catalytic activity. CONCLUSION: A BINAP‐Cu complex supported on hydrotalcite was prepared and used as a heterogeneous catalyst for the C─H activation of thiophenol under mild reaction conditions. Through a cascade C─H hydroxylation and further oxidation process, 2‐Sulfanylphenols and arylthioquinones could be obtained with moderate‐to‐good yields for a series of 2‐(phenylthio)phenol derivatives using the heterogeneous catalyst [Cu(binap)I]2 @HT. In addition, this heterogeneous catalyst showed good recylbility. © 2020 Society of Chemical Industry